2021
DOI: 10.3389/fmolb.2021.634479
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Modeling to Interrogate Microbial Disease: A Tale for Experimentalists

Abstract: The explosion of microbiome analyses has helped identify individual microorganisms and microbial communities driving human health and disease, but how these communities function is still an open question. For example, the role for the incredibly complex metabolic interactions among microbial species cannot easily be resolved by current experimental approaches such as 16S rRNA gene sequencing, metagenomics and/or metabolomics. Resolving such metabolic interactions is particularly challenging in the context of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…that are known to be important in the context of CF lung disease. 20 However, we argue that this polymicrobial model can be used as a starting point to identify mechanisms that can be further vetted in more in vivo -like systems.…”
Section: Discussionmentioning
confidence: 99%
“…that are known to be important in the context of CF lung disease. 20 However, we argue that this polymicrobial model can be used as a starting point to identify mechanisms that can be further vetted in more in vivo -like systems.…”
Section: Discussionmentioning
confidence: 99%
“…Other applications could be the con rmation of results obtained when using metabolic, in spatial distribution, and inter-intra-species competition modeling. Metabolic modeling has recently been described to be used to probe interactions hypothesized to drive gut health and microbial community structure to better understand microbial disease and microbial imbalance 37 . Spatial distribution, interspecies and intraspecies competition, resistance to host defense and antimicrobial agents, has been widely modeled before, for various communities 24,[38][39][40] .…”
Section: Discussionmentioning
confidence: 99%
“…Other airway model studies have also reported changes in P. aeruginosa behavior when grown on lung epithelial cells, such as altered gene expression or an increase in antibiotic tolerance 35,51 . A potential cause of increased P. aeruginosa growth in the healthy model could be due to the influence of epithelial cell metabolites 52,53 . While host-microbe metabolic interactions in CF airway infections have yet to be fully understood due to the complex and polymicrobial nature of these infections, there is evidence that the effectiveness of antibiotics can be modulated by host metabolites 54 such as lactate 55 .…”
Section: Discussionmentioning
confidence: 99%